Хімічно активоване буре вугілля як електроди для суперконденсаторів з органічним електролітом - Tamarkina, Y. V.; Mysyk, R. D.; Kucherenko, V. A.; Shendrik, T. G. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2009)
With a view of designing novel materials for electric double layer capacitors, activated carbons prepared by thermolysis of Alexandriya brown coal with KOH at various KOH/coal ratios (RКОН -0,2-1,0 g/g) were studied. Materials produced at RКОН >0,5 g/g were shown to have satisfactory electrode characteristics in organic-based capacitors within the electrolyte voltage window (tetraethylammonium tetrqfluoroborate, voltages up ~3 V). It was established that the maximum gravimetric capacitance is exhibited by the material prepared at RКОН =1 g/g- The sample prepared at RКОН =0,5 g/g demonstrated the minimum capacitance loss on increasing the current density. Differences in the behavior of samples were explained by different portions of pores less than 1 nm in diameter.